Screening of strains for biopurification of soybean molasses to produce functional soybean oligosaccharides - YANG Ran, ZHONG Xiufang, TANG Yanbin, MA Jinghao, TIAN Shubin, DU Yihua, FAN Guangsen (Zhongguo niangzao)
Soy molasses is rich in soybean isoflavones, soybean oligosaccharides, soybean protein, and sucrose, etc. The main components of soybean oligosaccharides are sucrose, raffinose, stachyose and so on. In order to obtain strains for biopurification of soybean molasses to produce functional soybean oligosaccharides, based on 210 strains (46 yeast strains, 45 bacterium strains and 119 mold strains) isolated from Baijiu brewing environment, using the sucrose retention rate, raffinose retention rate, stachyose retention rate, and mannotriose content in soybean molasses as the inspection indexes, the strains were preliminarily screened and rescreened. Cluster analysis and characterization research of raffinose and hydrothreose in biopurification soybean molasses of rescreened strains were carried out. The results showed that yeasts were excellent strains for biopurification soybean molasses to produce functional soybean oligosaccharides. The cluster analysis of rescreened strains showed that cluster 2 yeast strains included yeasts YS214, YT112, YT312, YA176, YA281, YT141, YA382, YA133, and YT344, the sucrose retention rates of them were less than 10% after processing soybean molasses, while the retention rates of raffinose and stachyose were greater than 85%, which were suitable for biopurification soybean molasses to produce functional soybean oligosaccharides.